DINAMIKA KONFLIK MASYARAKAT DAN PEMERINTAH TERHADAP DAMPAK PERTAMBANGAN BATU BARA DI KOTA SAMARINDA - Sry Reski Mulka (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
With the availability of mineral resources in the form of coal in the city of Samarinda, it is an advantage for the city government in increasing regional income in the form of taxes and royalties, but with the existence of coal mining activities that have obtained an operating permit from the Samarinda City Government, it has triggered a conflict between the Samarinda City Government. with the local community. This conflict-related relationship cannot be separated from the ecological impacts caused by coal mining activities, in which the government has no commitment to maintaining the quality of the community's environment. In this study, the author wants to analyze how the dynamics of the conflict that occurs between civil society and the Samarinda City Government related to coal mining activities in Samarinda City. In the preparation of this study the authors used qualitative methods. he result of the research is that there is public distrust of the Derah Government in establishing relationships, in the aspect of negotiating the principle that there are differences in views between the government and residents regarding land management, and the needs of residents who are hindered due to the impact of coal mining.